أثر إدارة المعرفة على إتخاذ القرار في المؤسسة دراسة حالة مديرية الصيانة سونطراك الأغواط - علي واعر ياسين; بن برطال عبد القادر (جامعة عمار ثليجي الاغواط, 2022)
This study aims to identify the impact of knowledge management in the Sonatrach Maintenance Directorate in Laghouat. To achieve the objectives of the study, a questionnaire was developed for the purpose of collecting information and data from the study sample, which was 30 employees, where a set of statistical methods were used using spss. There is also a statistically significant effect for the axis of knowledge acquisition and knowledge application. As for knowledge storage, distribution and dissemination of knowledge, there is no statistically significant effect The study also found that there were no statistically significant differences for knowledge management on decision-making in the Maintenance Directorate of Sonatrach in Laghouat, due to (age, educational level, occupational level, experience.)